Fatores de influência e funções técnicas no projeto de máquinas agrícolas: uma contribuição teórica - Marini, Vinicius Kaster (2007)
Being aware of the increasing complexity of the current designs of agricultural machinery, and about the further progress of this characteristic that constitutes trend for the next developments, the implementation of structured and systematic models for approaching the design information on agricultural machinery becomes an issue. The present work intends to define an information platform for understanding the influencing factors on design and its placement as a set of directions for the deployment of the function structure. Such modeling is done from the undertaking of an exploratory research on the knowledge areas of agricultural machinery and mechanization, and engineering design of mechanical systems; its implementation is done using the representation structure of the agricultural machinery development process as main resource, in form of a set of tables resembling an electronic spreadsheet. The influencing factors on design are defined from basic characteristics of the agricultural machine lifecycle phases after its production and manufacturing, and are configured through a model of classes and attributes, which makes possible to define a methodology for their survey. The function structure is constituted from the systems engineering approach, in the form expressed by the theory of technical systems, and is deployed from the analysis of the agricultural operation. Such constitutes basis for declaring the global function and for deploying the auxiliary function chains taking the types of auxiliary effects defined in the theory of technical systems as criteria for their definition. The proposal on modeling the function structure includes considering the control actions of the agricultural machine, from the known definitions of manual action and processed action. The modeling results are evaluated using the case study technique with a centrifugal fertilizer spreader as case unit. An information model is proposed, which gathers and classifies the influencing factors on design by classes and attributes, and establishes general considerations for deploying the function structure. Through this approach, the declaration of the influencing factors on design is formalized and so it is taken in consideration for deploying the function structure. This structure is based upon the definition of the agricutltural operation to be executed by the machine, is declared in form of a global function and is deployed by the usage of heuristics which involve semantic and physical interpretation, known from the literature. The final representation of the function chain involves the physical understanding of the necessary mechanical actions to accomplish the intended transformation, and includes control considerations, developed from the understanding of the closed loop cycle. Such results compose a useful systematic model for improving information traceability in the agricultural mechnery development process